Approximation of The Lower Operator in Nonlinear Differential Games with Non-Fixed Time - Iskanadjiev, I.M. (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
Approximate properties of the lower operator in nonlinear differential games with non-fixed time are studied.